Municipal Local Economic Development and the Multiplier effect: Piloting a Community Enterprise Identification Method in South Africa and Namibia (Commonwealth Journal of Local Governance, 2011)
Local Economic Development (LED) is a contested concept in southern Africa, and has become synonymous with delivery of generic job-creation projects, often grant-dependent and unsustainable. Municipal LED has followed this pattern in South Africa since 1994, with little lasting success. Each local economy is unique, and has its own problems and opportunities. The ’Plugging the Leaks’ method recognizes that communities themselves know best how money enters and exits their area. By asking people to analyse their local economy as a 'leaky bucket', the method puts control back in the hands of local people, rather than external experts, and allows them to analyse their own local economy to identify gaps and opportunities for enterprise. By better networking and working collectively to improve their local economy, local communities are able to re-circulate cash internally. This circulation of cash is explained as the local multiplier effect in the workshops. A pilot process of running ‘Plugging the Leaks’ workshops in low income communities in South Africa and Namibia revealed that spending choices in these communities are severely limited in a context where there is no effective welfare state. Therefore, empowerment with this method came from the discovery of collective action and networking, rather than from individual spending choices. Local start-up business tends to be limited to survivalist and copy-cat one-person ventures, and are a last resort when formal employment is absent. In this context collective enterprise offers the necessary empowerment for people to attempt financially sustainable ventures that respond to a gap in the local economy. The pilot project is attempting to show that municipal LED staff can play the role of facilitator for initiating the enterprise-identification process and further mobilise state enterprise support agencies around the locus of LED, without crossing the line between facilitation and implementation of ’projects’.